Pengolahan Air Hujan Sebagai Alternatif Pemenuhan Air Bersih di Perumahan Anging Mammiri Kota Makassar - Rahim, Abdul; Sulfanita, Andi; Didi, Andi Bustan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The use of rainwater as an alternative source of clean water is also very potential when applied in residential areas or residential areas. In Karunrung Village, Rappocini District, Makassar City, there is still a lack of adequate clean water supply, some people use shallow wells but in the event of a drought, the shallow wells experience drought. This study aims to find out how much discharge is the influence of rainwater treatment to meet the need for clean water in Anging Mammiri Housing. This study uses a descriptive qualitative research method. The results of the study show that the amount of potential rainwater discharge that can be produced into clean water needs is obtained from calculating the amount of rainwater that can be managed into clean water which amounts to 86,993.8 liters/day and the amount of clean water needed by the residents of Anging Mammiri which amounts to 51,750 liters/day so that rainwater treatment is able to meet the clean water needs of the community in Anging Mammiri Housing as much as 52% per day.